A moisture absorbing gel electrolyte enables aqueous and flexible supercapacitors operating at high temperatures. Issue 35 (27th August 2019) - Liu, Lingyang; Dou, Qingyun; Sun, Yinglun; Lu, Yulan; Zhang, Qingnuan; Meng, Jianing; Zhang, Xu; Shi, Siqi; Yan, Xingbin
Abstract : A "water-in-salt" gel electrolyte with superior water-retention capability enables aqueous flexible supercapacitors to operate at high temperature up to 120 °C. Abstract : Gel electrolytes are of great importance for supercapacitors (SCs) operating at high temperatures. However, it is a fundamental challenge for SCs using aqueous gel electrolytes at elevated temperatures to ensure good work durability due to the evaporation of water. Here we report a "water-in-salt" gel electrolyte that exhibits superior water-retention and even water-absorption capability. What is noteworthy is that a quasi-solid-state SC utilizing the gel electrolyte is able to work and exhibit long cycling life across a wide temperature range from room temperature up to 120 °C in an extremely dry atmosphere, representing the best record among the previously reported aqueous gel-based SCs, as far as we know. This strategy may provide a new way to develop reliable aqueous gel electrolytes for SCs operating at high temperatures.